Evolutionary Relationships and Range Evolution of Greenhood Orchids (Subtribe Pterostylidinae): Insights From Plastid Phylogenomics - Nargar, Katharina; O’Hara, Kate; Mertin, Allison; Bent, Stephen J.; Nauheimer, Lars; Simpson, Lalita; Zimmer, Heidi; Molloy, Brian P. J.; Clements, Mark A. (Frontiers in Plant Science, 2022)
Australia harbours a rich and highly endemic orchid flora with over 90% of native species found nowhere else. However, little is known about the assembly and evolution of Australia’s orchid flora. Here, we used a phylogenomic approach to infer evolutionary relationships and range evolution in Pterostylidinae (Orchidoideae), the second largest subtribe in the Australian orchid flora, comprising the genera Pterostylis and Achlydosa. Phylogenetic analysis of 75 plastid genes provided well-resolved and supported phylogenies. Intrageneric relationships in Pterostylis were clarified and monophyly of eight of ten sections supported. Achlydosa was found to not form part of Pterostylidinae and instead merits recognition at subtribal level, as Achlydosinae. Pterostylidinae were inferred to have originated in temperate eastern Australia in the early Oligocene, coinciding with the complete separation of Australia from Antarctica and the onset of the Antarctic Circumpolar Current, which led to profound changes in the world’s climate. Divergence of all major lineages occurred during the Miocene, accompanied by increased aridification and seasonality of the Australian continent, resulting in strong vegetational changes from rainforest to more open sclerophyllous vegetation. The majority of extant species were inferred to have originated in the Quaternary, from the Pleistocene onwards. The rapid climatic oscillations during the Pleistocene are regarded as an important driver of speciation in Pterostylidinae. The subtribe underwent lineage diversification mainly within its ancestral range, in temperate eastern Australia. Long-distance dispersals to southwest Australia commenced from the late Miocene onwards, after the establishment of the Nullarbor Plain, which constitutes a strong edaphic barrier to mesic plants. Range expansions from the mesic into the arid zone of eastern Australia (Eremaean region) commenced from the early Pleistocene onwards. Extant distributions of Pterostylidinae in other Australasian regions, such as New Zealand and New Caledonia, are of more recent origin, resulting from long-distance dispersals from the Pliocene onwards. Temperate eastern Australia was identified as key source area for dispersals to other Australasian regions.